Behavioral inflexibility in fragile X syndrome: Accounts from caregivers and self-advocates - Jones, Angelina; Kang, Sungeun; Shaffer, Rebecca C.; Erickson, Craig A.; Schmitt, Lauren M. (Frontiers in Psychology, 2023)
Introduction Behavioral difficulties in individuals with fragile X Syndrome (FXS) are one of the primary reasons families seek medical and psychological support. Among these, behavioral inflexibility is very common, and when left untreated, can negatively impact quality of life for the individuals with FXS and their families. Behavioral inflexibility refers to the difficulty in changing one’s behaviors based on environmental demands or social contexts, thus impeding daily functioning, opportunities for learning, and social interactions. In addition to the individual and family impact, behavioral inflexibility is often recognized as a defining phenotype of FXS and appears to be specific to FXS when compared to other genetic forms of intellectual disability. Despite the pervasiveness and severity of behavioral inflexibility in FXS, there are limited measures that adequately assess behavioral inflexibility in FXS. Methods We conducted semi-structured virtual focus groups with 22 caregivers, 3 self-advocates, and 1 professional to gather key stakeholders’ perspectives on and experiences of inflexible behavior observed in FXS. Audio-recordings from focus groups were transcribed using NVivo, then verified and coded. Two trained professionals reviewed codes to extract primary themes. Results Six themes were extracted: (1) Intolerance of change, (2) Intolerance to uncertainty, (3) Repetitive interests and behaviors, (4) Family impact, (5) Change in behavior across the lifespan, and (6) Impact of the COVID pandemic. Our findings show common examples of these themes included intolerance to disruption to routine, perseverative questioning, watching the same things over and over, and caregivers having to extensively pre-plan for events. Discussion The purpose of the current study was to gain key stakeholders’ perspectives via focus groups to elicit information and understand patterns of inflexible behaviors in FXS, with the goal of developing a disorder-specific measure to accurately assess behavioral inflexibility across the lifespan and in response to treatment. We were able to capture several phenotypic examples of behavioral inflexibility in FXS as well as their impact on individuals with FXS and their families. The wealth of information gained through our study will aid in our next steps of item generation for measure development of Ratings of Inflexibility in Genetic Disorders associated with Intellectual Disability – Fragile X Syndrome (RIGID-FX).